2002
DOI: 10.1128/aac.46.6.1896-1905.2002
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Resistant Human Immunodeficiency Virus Type 1 in Patients Receiving Fusion Inhibitor (T-20) Monotherapy

Abstract: The synthetic peptide T-20 (enfuvirtide) represents the first of a new class of antiretroviral compounds to demonstrate in vivo potency by targeting a step in viral entry. T-20 inhibits a conformational change in the human immunodeficiency virus type 1 (HIV-1) transmembrane glycoprotein (gp41) that is required for fusion between HIV-1 and target cell membranes. The initial phase I clinical trial of T-20 treatment for HIV-infected patients thus provided a unique opportunity to evaluate the emergence of resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
1,433
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,483 publications
(1,446 citation statements)
references
References 26 publications
11
1,433
0
2
Order By: Relevance
“…Similar to results with other antiviral agents, however, ENF-resistant HIV-1 variants may emerge under the selective pressure of ENF (26,32,39,42) whenever the treatment fails to completely suppress viral replication in vivo. Understanding the determinants of, and the constraints to, the development of resistance to ENF is essential for the optimization of the clinical use of this new class of inhibitors.…”
Section: Acquired Human Immunodeficiency Virus Type 1(hiv-1) Resistanmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar to results with other antiviral agents, however, ENF-resistant HIV-1 variants may emerge under the selective pressure of ENF (26,32,39,42) whenever the treatment fails to completely suppress viral replication in vivo. Understanding the determinants of, and the constraints to, the development of resistance to ENF is essential for the optimization of the clinical use of this new class of inhibitors.…”
Section: Acquired Human Immunodeficiency Virus Type 1(hiv-1) Resistanmentioning
confidence: 60%
“…ENF binding to HR1 is thought to compete with the folding of the HR2 domain onto HR1, thus preventing Env-mediated membrane fusion (1,5,17). Accordingly, viral variants selected both in vitro and in vivo in the presence of ENF carry resistance mutations in the HR1 domain (35,42). Mutations in HR2 have also been described in virus from treated patients and are thought to exert a compensatory role through reinforcement of the interaction between HR1 and HR2 in the context of a mutated HR1 (2,25,46).…”
mentioning
confidence: 99%
“…Viral infectivity was then determined by adding the solutions to the wells of a 96-well plate coated with TZM-bl indicator cells (30). Virions were allowed to infect cells for 1 h after which the wells were washed twice with PBS followed by the addition of 0.2 ml of culture medium.…”
Section: Stimulation Of Human Pmn and Antimicrobial And ␣-Defensin Asmentioning
confidence: 99%
“…[28] In addition, one of the consequences of high and frequent administration is the emergence of T-20 resistant strains of HIV. [37] 3.3. Nucleoside and Nucleotide Reverse Transcriptase Inhibitors (NRTIs and NtRTIs) Seven nucleoside reverse transcriptase inhibitors (NRTIs) have been licensed for marketing (Figure 4), however the production of zalcitabine (ddC) has been discontinued due to the production of more effective replacement NRTI drugs.…”
Section: Fusion Inhibitorsmentioning
confidence: 99%
“…Wang et al reported multivalent oligomannose dendrons conjugated via copper catalyzed 'click' chemistry to first, second and third generation alkyne functionalized dendritic scaffolds that were shown to bind to DC-SIGN expressing cells. [123] Using glycan microarrays for direct interactions and competition assays with IgG 2G12 (an antibody that targets the glycans on gp120), these authors demonstrated that the dissociation constant of multivalent oligomannose dendrons (37) inversely correlated to an increase dendrimer generation as well as to the number of mannose units (Man 4 or Man 9 ). Although the in vitro assays demonstrated the nanomolar binding affinities due to multivalency of the glycodendrons, evidence for HIV-1 inhibition by trans-infection was not shown.…”
Section: Polymeric Dc-sign Antagonistsmentioning
confidence: 99%